Diabetes Mellitus tipo 2 e uso de ácido acetilsalicílico: relação dos níveis de 11-dihidro tromboxano urinário e variáveis clínicas, genéticas, hemostáticas e bioquímicas - Lillian Harboe Goncalves (2010)
Acetylsalicylic acid (ASA) is the antiplatelet agent mostly used because it inactivates the enzyme cyclo-oxygenase-1, preventing the production of thromboxane A (TXA ). This study was delineated in order to investigate the effect of ASA on the inhibition of TXA,in diabetic patients taking ASA daily, to prevent the occurrence of atherothrombotic event. The study group was constituted of patients who attended the diabetes mellitus 2 outpatient clinic of the Centro de Especialidades Médicas da Santa Casa de Belo Horizonte. During the study, two samples of urine and blood were obtained from each patient. The first one was collected before starting use of ASA and the second one after fifteen days taking the drug. These samples were analyzed to determine the urinary levels of a TXA metabolite (11-dehydro thromboxane B 2(11-dhTXB)). Laboratory tests also included determination of lipidic profile, glycated hemoglobin, D-dimer, C-reactive protein, platelets count and molecular analysis for both GPIIIa and COX-1 polymorphisms. The studied group had 81 members, with female predominance (71%) and medium age of 57.39±9.8 years. Patients median value for urinary 11-dhTXB2 before ASA intake was 179.00 pg/mg creatinine. After 15 days taking ASA they had median of 51.00 pg/mg creatinine. There was significant difference between medians (p=0.00). Reduction of at least 90% on urinary 11-dhTXB levels was not found in 86% of the patients. Body mass index =26 kg/m 2 2 presented a significant association with reduction of urinary 11-dhTXB levels (p=0,010) as shown by multiple logistic regression model. Other clinical and laboratory variables (lipidic profile, glycated hemoglobin, D-dimer, C-reactive protein, platelets count and molecular analysis for both GPIIIa and COX-1 polymorphisms) showed no association. Even though this study had a small population size, the results achieved show that diabetic patients differ in their response to ASA and may not be protected against the occurrence of atherothrombotic events. Data analysis corroborate the results of meta-analyses published in 2009 and 2010 showing that, for primary prevention, some diabetic patients do not benefit from ASA effect as an inhibitor of TXA Key words: acetylsalicylic acid, thromboxane, platelet, diabetes mellitus 2.